Assessing Overtraining Syndrome in Competitive Athletes: Biomarkers, Screening Tools, and Clinical Correlates - Wajerowska, Weronika; Nawracaj, Barbara; Browarny, Sonia; Dubniański, Bartosz; Fudali , Kacper; Hejnowicz, Mateusz; Tymec, Jan; Stawińska, Kornelia (Quality in Sport, 2026)
Background Overtraining syndrome (OTS) is a multifactorial clinical condition resulting from an imbalance between training load and recovery. It affects up to 64% of male and 60% of female athletes at least once during their career and carries significant consequences for physical performance, hormonal balance, immune function, and mental health. Despite its prevalence, OTS remains poorly defined and difficult to diagnose due to the absence of a single validated biomarker and substantial overlap with other conditions common in athletic populations. Aim To review the current evidence on the pathophysiology, diagnostic approaches, biomarkers, and prevention strategies related to overtraining syndrome, and to evaluate the utility of existing and emerging diagnostic frameworks. Material and methods A thorough analysis has been conducted following PRISMA recommendations. The research data have been derived from scientific databases of Embase, PubMed and Google Scholar. Key word choice was based on their relevance to the review subject beforehand. Results OTS arises from the interaction of metabolic, immunological, neuroendocrine, and autonomic dysregulation. The EROS study identified over 45 candidate biomarkers, yet none proved universally diagnostic. Multidomain assessment combining hormonal, immunological, and autonomic markers demonstrated superior diagnostic value over any single parameter. Prevention relies on integrated monitoring of training load, recovery, nutrition, sleep, and psychological well-being. Summary OTS diagnosis requires comprehensive clinical evaluation and systematic exclusion of alternative aetiologies. No pathognomonic marker exists; therefore, multiparametric frameworks remain the most reliable diagnostic approach. Early detection and prevention through multidimensional athlete monitoring constitute the most effective clinical strategy.